2016
DOI: 10.1090/conm/663/13356
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Order Biases in Elliptic Curve Fourier Coefficients in Families

Abstract: and consider the k th moments A k,E (p) := t mod p a Et (p) k of the Fourier coefficients a Et (p) := p + 1 − |E t (F p)|. Rosen and Silverman proved a conjecture of Nagao relating the first moment A 1,E (p) to the rank of the family over Q(T), and Michel proved that the second moment is equal to A 2,E (p) = p 2 + O p 3/2. Cohomological arguments show that the lower order terms are of sizes p 3/2 , p, p 1/2 , and 1. In every case we are able to analyze, the largest lower order term in the second moment expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Essentially, the proof of (2.1) in [MMRW16] translates to the proof of a total point count on the threefold M defined in (1.4).…”
Section: The Second Moment and The Point Count On The Kummer Threefoldmentioning
confidence: 99%
See 2 more Smart Citations
“…Essentially, the proof of (2.1) in [MMRW16] translates to the proof of a total point count on the threefold M defined in (1.4).…”
Section: The Second Moment and The Point Count On The Kummer Threefoldmentioning
confidence: 99%
“…The terms f i (p) where i < 4 are called the lower order terms and i is the degree of that term. In [ACF + 18] and [MMRW16] the authors studied the second moments M 2,p (F k ) of the families of elliptic curves F k . Most of their examples are pencils of cubics (1.3)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this and the next section we amass more evidence for the Bias conjecture by demonstrating negative bias in additional one-parameter families of elliptic curves. See [MMRW,Mi1,Mi3] for earlier calculations on the subject. The families studied are amenable to direct calculation; thus these are not generic families but ones chosen so that the resulting Legendre sums are tractable.…”
Section: Linear One-parameter Families Of Elliptic Curvesmentioning
confidence: 99%
“…The prime example is that of whether or not their is excess rank in families of elliptic curves (see [BMSW] for a nice summary of data and conjectures); while earlier investigations indicated that such bias might persist, later studies [W] went far enough to see the average rank drop, and new random matrix models have been introduced that have the correct limiting behavior and successfully model the observed behavior for small conductors [DHKMS1,DHKMS2]. There are now many results on lower order terms in families, such as [HKS,MMRW,Mil2,Yo1], and the hope is that the methods of this paper can be extended to include these to refine estimates for finite conductors.…”
mentioning
confidence: 99%